The Role of Interleukin-1 and Interleukin-6 in the Development of Acute Myocardial Infarction - Pejkov, Hristo; Elizabeta Srbinovska-Kostovska; Boshev, Marjan; Slavica Josifovska; Panov, Sasho; Sashko Kedev (My University, 2023)
Certain cytokines as interleukin-1 (IL-1) and interleukin-6 (IL-6) are produced by the neutrophils and macrophages localized in the atheromatous plaques. The levels of circulating inflammatory cytokines IL-1 and IL-6 are found to be significantly increased in patients with ST-Segment Elevation Acute Myocardial Infarction (STEMI). In a group of 38 patients with STEMI, the levels of IL-1ß and IL-6 were determined in the coronary circulation (CC) by analysis of aspirates from the culprit lesions and the levels of these inflammatory markers in the systemic (peripheral) circulation (SC) during STEMI and six months after STEMI. Coronary angiography (CA) and percutaneous coronary intervention (PCI) were performed in all patients and the levels of cytokines were determined by the ELISA method. By examining the levels of IL-1ß and IL-6, the aim of this study was to determine their predictive value in short-term prognosis. In the acute phase (STEMI) there was a statistically significant difference between the mean values of IL-1ß (p=0, 000000) and IL-6 (p=0, 026204) in the samples of CC and SC, respectively. Results from the six months of follow-up showed that there were statistically no significant differences between the mean values of IL-1ß and IL-6 in the CC and SC. Moderate and low-positive correlation between the mean values of IL-1ß (r=0,6816; p=0,000) and IL-6 (r=0,4291; p=0,000) in CC and SC was observed at the sixth month of follow-up. In conclusion, our results confirm that IL-1ß and IL-6 are linked to the progression of Coronary Artery Disease (CAD) and should be considered as predictive markers.
Keywords: acute myocardial infarction; coronary artery disease; cytokines; ST-elevation myocardial infarction; interleukins